Um estudo comparativo entre os grupos pessoenses de forró: Cabras de Mateus e Duquinha e Banda - Silva, Jaqueline Alves da (2011)
Taking into consideration the various gradations which the polarized idea of traditional forró and electronic forró can hold, this study aimed at examining the main features which constitute the differences and similarities between the forró of Cabras de Mateus and that of Duquinha e Banda, both from João Pessoa, concerning their aesthetico-structural features. It also aimed at getting acquainted with the conceptions and representations of those who were interviewed about forró, as well as the relation between this musical genre and the other aspects which make it a socio-cultural manifestation, such as dance, clothing, and its relation to the media, taking into account some implications as to work space and conceptions of the world to those who make a living from making this kind of music. To do this, we adopted the multiple-case ethnographic study as the investigation strategy, following a socio-cultural orientation and a multiperspectivistic approach. Constituting two current trends in the cultural industry in the field of music, i.e. music intended for wide consumption and for segmented consumption, the results indicated that both kinds of forró are structured in global environments, although distinct ones, since, for those who do the called traditional forró, their conceptions and practices related to the discourse of nostalgia and tradition are erected on the basis of an "imaginary landscape" in the Northeast or Northeast a historically constructed. The results also demonstrate that the process of reframe of forró, placed here by electronic forró, does not occur in a peaceful manner, involving therefore the demarcation of territories and marketing disputes, as well as the fact that the symbolic order specifies that nurtures the creation art has been redefined by the market logic.